Heterogeneous Agents, Human Capital Formation and International Income Inequality - Haris Munandar (Tinbergen Institute, 2008)
The paper examines the effect of heterogeneity in individual human capital formation on cross-country income inequality. It considers a two-country model of overlapping generation heterogeneous economies with the following features: (1) individuals are heterogeneous with respect to inborn ability and parental human capital; (2) intergenerational transfers take place via public investment in education financed by tax, and parental education; (3) due to variation in individual human capital, we have endogenous heterogeneity both in labor supply and in parents' participation in self-educating their offspring. Besides exploring cross-country variation in public education, how its low level can lead to a poverty trap and how its high level can result in an increasing society's effective human capital, we study the effects of capital markets integration, in equilibrium, on the intra-generational income inequality in both the investing and receiving countries.
Keywords: D91; E25; H52; 330; Heterogenous Agents; Human Capital; Poverty Efrap; Income Inequality; Humankapital; Soziale Ungleichheit; Armut; Einkommensverteilung; Zwei-Länder-Modell; Overlapping Generations; Theorie